The Unimportant Differences - Vanderbilt, Amy (Tufts Archival Research Center, 2006)
Amy Vanderbilt explains her awareness and appreciation of people, equality and friendship and describes how her son exemplified this in his disregard for race when meeting a lady on the bus.